On the Utility of Literary Fictions: An Approach from the Philosophy and Neuroscience of Narrative (Tábano, 2025)
The article aims to highlight the utility of fictions, particularly literary ones, for human life. The approach we propose is amphibious since it seeks to address this utility from both a philosophical perspective and, on the other hand, from the neuroscience of narrative. The presentation is divided into two main sections. The first explores the concept of fiction and explicitly addresses the need for human beings to create fictions in order to survive and form communities. The second provides an explanation of the primary function of imitation, incorporating the concept of mirror neurons, and lists the most relevant utilities of fictions for human life, such as: mental training to face real-life situations, the promotion of social cohesion, prosocial behaviors, social cognition, the internalization of moral norms, the consolidation of community identity, and the formation of personal identity.
Keywords: Philosophy; Literature; Neuroscience; Fiction; Utility